Foreign body in the hypopharynx--an unusual presentation. Issue 4 (July 1996) - Sheikh, S; Natarajan, B; Johnston, A
Abstract : A case is described of a foreign body (a metallic paper clip) in the hypopharynx of an 18 month old child presenting with recurrent respiratory tract infections. The child was treated with antibiotics at two accident and emergency departments without any benefit. A high degree of suspicion is necessary in young children, as a history of ingestion of a foreign body may not be forthcoming. It is important to be aware of the possibility of a foreign body in young children, particularly when the clinical presentation is atypical.